2021
DOI: 10.3390/v13061076
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2, Symptom Profiles and Sero-Neutralization in a Suburban Area, France

Abstract: The World Health Organisation recommends monitoring the circulation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We investigated anti–SARS-CoV-2 total immunoglobulin (IgT) antibody seroprevalence and in vitro sero-neutralization in Nancy, France, in spring 2020. Individuals were randomly sampled from electoral lists and invited with household members over 5 years old to be tested for anti–SARS-CoV-2 (IgT, i.e., IgA/IgG/IgM) antibodies by ELISA (Bio-rad); the sero-neutralization activity was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Locally, another study evaluated the seroprevalence in laboratory staff of the same university hospital. This one was almost equal to that of local general population ( 5 , 7 ) and lower compared to HCWs. When handling samples, laboratory technicians are better protected than HCWs, in particular through the use of microbiological safety stations in addition to PPE ( 7 ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Locally, another study evaluated the seroprevalence in laboratory staff of the same university hospital. This one was almost equal to that of local general population ( 5 , 7 ) and lower compared to HCWs. When handling samples, laboratory technicians are better protected than HCWs, in particular through the use of microbiological safety stations in addition to PPE ( 7 ).…”
Section: Discussionmentioning
confidence: 61%
“…SARS-CoV-2 seroprevalence of Nancy University Hospital HCW (5.1%) was lower than that in the Whole Northeast of France (6.7%) but higher to that of the Nancy Town (2.1 %) metropolis ( 5 ). Yet, seroprevalence was not associated with working in a COVID-19 unit.…”
Section: Discussionmentioning
confidence: 62%
“…We ensured a sample size n > 500. When investigations of such scale were not available for a nation, we included studies that reported the seroprevalence in provinces 26,45 , counties 37 , regions 42 , governates 39 , major cities and towns 20,29,32,36,40 , districts 54 , or municipalities 27,30,35 , with populations that were representative of the general population of the nation.…”
Section: Methodsmentioning
confidence: 99%
“…For the reasons above, analyses including ‘former’ in the same reference group as ‘never’ smokers when estimating the relative risk of COVID-19 among ‘current smokers’ may yield downwards biased estimates of associations, reported in previous studies based on such a comparison [1517].…”
Section: Introductionmentioning
confidence: 99%